ANALISIS PERBANDINGAN MODEL KERUSAKAN PERKERASAN LENTUR ANTARA MDPJ 2024 SERTA ASPHALT INSTITUTE DAN AASHTO MEPDG - Kevin Briant Pasaribu; Taqia Rahman; Latif Budi Suparma (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Flexible pavement plays a critical role in supporting economic growth and connectivity. However, overloading heavy vehicles accelerates structural damage such as fatigue cracking and rutting. This study aims to compare the damage prediction models of the 2024 Manual Desain Perkerasan Jalan (MDPJ), Asphalt Institute, and AASHTO MEPDG using KENPAVE simulation across four road classifications in Indonesia. A quantitative descriptive method was employed, analyzing design data from MDPJ 2024, with purposive sampling representing varied traffic loads. KENPAVE software provided horizontal and vertical strain outputs essential for damage calculations via transfer functions of the three models. Results indicated that MDPJ 2024 predicts higher Equivalent Single Axle Load (ESAL) values for fatigue cracking and rutting than international methods, showing optimistic durability estimations. However, differences in permanent deformation predictions, especially compared to AASHTO MEPDG, suggest the need for local calibration. The study concludes that while all models identify fatigue cracking as the dominant failure mode, calibration with field data is essential to validate predictions and optimize pavement design. Future research should focus on empirical validation and environmental factors to improve the national design standards. These findings support enhancing pavement life and cost-efficiency for Indonesia's infrastructure management.